Genetic Defects and Pro-inflammatory Cytokines in Parkinson's Disease - Magnusen, Albert Frank; Hatton, Shelby Loraine; Rani, Reena; Pandey, Manoj Kumar (Frontiers in Neurology, 2021)
Parkinson's disease (PD) is a movement disorder attributed to the loss of dopaminergic (DA) neurons mainly in the substantia nigra pars compacta. Motor symptoms include resting tremor, rigidity, and bradykinesias, while non-motor symptoms include autonomic dysfunction, anxiety, and sleeping problems. Genetic mutations in a number of genes (e.g., LRRK2, GBA, SNCA, PARK2, PARK6, and PARK7) and the resultant abnormal activation of microglial cells are assumed to be the main reasons for the loss of DA neurons in PD with genetic causes. Additionally, immune cell infiltration and their participation in major histocompatibility complex I (MHCI) and/or MHCII-mediated processing and presentation of cytosolic or mitochondrial antigens activate the microglial cells and cause the massive generation of pro-inflammatory cytokines and chemokines, which are all critical for the propagation of brain inflammation and the neurodegeneration in PD with genetic and idiopathic causes. Despite knowing the involvement of several of such immune devices that trigger neuroinflammation and neurodegeneration in PD, the exact disease mechanism or the innovative biomarker that could detect disease severity in PD linked to LRRK2, GBA, SNCA, PARK2, PARK6, and PARK7 defects is largely unknown. The current review has explored data from genetics, immunology, and in vivo and ex vivo functional studies that demonstrate that certain genetic defects might contribute to microglial cell activation and massive generation of a number of pro-inflammatory cytokines and chemokines, which ultimately drive the brain inflammation and lead to neurodegeneration in PD. Understanding the detailed involvement of a variety of immune mediators, their source, and the target could provide a better understanding of the disease process. This information might be helpful in clinical diagnosis, monitoring of disease progression, and early identification of affected individuals.